Peptídeos natriuréticos e angiotensina-(1-7) durante o processo de ovulação em bovinos - Santos, Joabel Tonellotto dos (2015)
Ovulation is controlled by a complex and dynamic interaction of factors, including endocrine and vasoactive mechanisms, cellular messengers and activating enzymes. It is well established that locally produced factors exert pivotal roles during ovulation. Some peptides such as angiotensin II (Ang II) and Natriuretic Peptides (NPs) have been prominent in local regulation of reproductive functions of mammals, beyond its systemic activities. Unlike angiotensin II (AngII), the role of angiotensin-(1-7) [Ang-(1-7)] has not been characterized in the ovary of mono-ovulatory species. In the first study, was evaluated the effect of Ang-(1-7) and its receptor (MAS) in the regulation of the ovulatory cascade. For this we used an in vitro model of supplementation with Ang- (1-7) or blocking its receptor on EREG mRNA expression in granulosa cells. Using an in vivo model, the intrafollicular injection of Ang-(1-7) antagonist (A-779 - MAS receptor inhibitor) was performed to evaluate the ovulation rate. Results showed that the Ang- (1-7) and A-779 inhibitor when in vitro culture, were not able to regulate to EREG mRNA expression. Likewise, the intrafollicular injection of A-779 did not block ovulation before the expected time of LH peak, suggesting that Ang-(1-7) has no role in the early ovulatory cascade in cattle. In the second experiment, the aim was to evaluate the pattern of mRNA expression in bovine granulosa cells for the Natriuretic Peptides Precursors (NPPs), receptors (NPRs) and key enzymes of this system after GnRH-induced ovulation in vivo. Using in vivo model main results have been shown the presence of several components of NPs system during ovulation in cattle, as well as increased mRNA expression for NPPC (natriuretic peptide precursor C) in granulosa cells after induction of ovulation with GnRH / LH. These results provide the first evidence that the C-type natriuretic peptide (NPC) is upregulated by LH and may be involved in ovulation and bovine luteinizing. Third study was conducted to answer like LH controls the mRNA expression for NPPC if this is up-regulated through EGF receptor (EGF-R). Moreover, we evaluated if the NPC regulates genes in ovulatory cascade and blockade EGF-R is capable of altering ovulation rate. For this we used an in vitro model of granulosa cell culture from large follicles (> 12 mm) and in vivo models to study ovulation, combined with intrafollicular injection and follicular dynamics and / or ovariectomy at strategic times. Our main results were: NPC does not regulate mRNA expression for amphiregulin (AREG) and EREG in vitro; NPPC mRNA coding is regulated by EGF-R but block EGF-R was not able to change the ovulation rate in bovines. These results suggest that the regulation and function of NPs during ovulation may differ between monovular and polyovular species.